2015
DOI: 10.1007/s11102-015-0655-4
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and prevalence of acromegaly, a nationwide study from 1955 through 2013

Abstract: The incidence of acromegaly in Iceland during the study period was much higher than earlier reports have indicated. During the last 9 years of the study 7.7 patients were diagnosed per million per year. At diagnosis, 38 % had developed hypertension and 10 % were diagnosed during follow up. This indicates the importance of endocrine disorders in the aetiology of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
48
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 10 publications
6
48
1
6
Order By: Relevance
“…Agustsson et al [6] performed a nationwide population study in Iceland and information was obtained from medical records at the National University Hospital, three district hospitals, all privately practicing endocrinologists and gynaecologists in the country, all radiology departments in Iceland, the Icelandic Cancer Registry, the department of pathology and the Icelandic Heart Association. Hoskuldsdottir et al [7] collected data from the medical records at the National University Hospital in Iceland, the largest hospital out of the capital, the largest private outpatient clinic in Iceland and from all endocrinologists treating adult patients in the country. Raappana et al [8] obtained information from Oulu University Hospital in which the great majority of patients with pituitary tumor from the four northernmost provinces of Finland are referred.…”
Section: Epidemiology Of Acromegalymentioning
confidence: 99%
See 4 more Smart Citations
“…Agustsson et al [6] performed a nationwide population study in Iceland and information was obtained from medical records at the National University Hospital, three district hospitals, all privately practicing endocrinologists and gynaecologists in the country, all radiology departments in Iceland, the Icelandic Cancer Registry, the department of pathology and the Icelandic Heart Association. Hoskuldsdottir et al [7] collected data from the medical records at the National University Hospital in Iceland, the largest hospital out of the capital, the largest private outpatient clinic in Iceland and from all endocrinologists treating adult patients in the country. Raappana et al [8] obtained information from Oulu University Hospital in which the great majority of patients with pituitary tumor from the four northernmost provinces of Finland are referred.…”
Section: Epidemiology Of Acromegalymentioning
confidence: 99%
“…Notably, the last two studies obtained information from the Swedish Pituitary Registry and the Spanish acromegaly registry, respectively, and the possibility of under-reporting cannot be excluded. It should be also pointed out that the two studies from Iceland [6, 7] cover the same population and have a significant overlap in the sources of their data; this could sway the overall results and they should not be considered as independent from each other. In most studies, there is a rather equal distribution of prevalence between males and females, with the exception of Daly et al [4] and Agustsson et al [6], in which men showed prevalence rates twice as high as those of women.…”
Section: Epidemiology Of Acromegalymentioning
confidence: 99%
See 3 more Smart Citations